Implementation of SIPD in Regional Financial Management: Evidence from Murung Raya Regency - Maximilianus Aditya Hersadjati; Irawan; Benius (Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyze the application of the regional government information system in enhancing the effectiveness and efficiency of financial management and administration. The regional government information system is a national digital system designed to integrate the entire regional financial cycle from planning, budgeting, execution, and reporting to evaluation. Using a mixed methods approach, this research combines quantitative analysis of regional budget, budget realization reports, and regional government information system metadata with qualitative analysis through interviews, observations, and questionnaires based on the DeLone & McLean model. The findings indicate that regional government information system implementation significantly contributes to improving expenditure realization accuracy, consistency between planning and budgeting documents, and reporting efficiency. The average user perception score for system quality reached 4.2, with performance impact rated very good (4.4). However, technical challenges such as server instability and limited digital human resources remain barriers to optimal implementation. This research reinforces the relevance of Musgrave’s theory on fiscal allocation efficiency and the DeLone & McLean model in evaluating public information systems.